The making of index numbers : a study of their varieties, tests, and reliability - Fisher, Irving; Pollak Foundation for Economic Research (New York : A.M. Kelley, 1967)
Trustworthiness of index numbers is one of the two chief purposes of the present book. In order to make the answer conclusive, all the formulae for index numbers which have been or could reasonably be constructed, have been investigated and tested in actual calculations based on actual statistical records.
Reprint of the 3d ed., rev., 1927.
Includes bibliographical references and index.
gau 02/08/2016
Loans
Keywords: Index numbers (Economics)